Research, innovation and technological performance in Germany - EFI Report 2009 - EFI - Commission of Experts for Research; Innovation (Commission of Experts for Research and Innovation (EFI), 2009)
On behalf of the German Federal Government, the Commission of Experts for Research and Innovation presents its second report. This was originally intended to be a “short” report, in which the key indicators of research and development were up-dated and commented on. However, the Expert Commission has decided to do much more than this, and recommends a series of measures to further strengthen the innovation potential of Germany. In particular in the present economic difficulties, research and innovation policies have a central role to play. The challenges faced are varied and were already named in the EFI Report 2008. The conditions for the financing of innovations are still not ideal in Germany. The weaknesses of the educational system are already having negative consequences and in the medium- term could represent an existential threat to the innovation potential. The high degree of specialisation in a few manufacturing sectors is an expression of the particular German strengths, but it also creates dependencies and risks. Because research and innovation policies are only effective over the medium- to long-term, these problems cannot be solved within a short period of time. But politicians must act more rapidly than in the past. The opportunity of introducing fiscal support for research and development has unfortunately not been seized, and the measures introduced by the Federal Government to improve investment financing are not at all convincing. In this second report we consider other fields of action: the intensification of knowledge and technology transfer, increasing the attractiveness of science as an employment opportunity, and the promotion of innovation processes in small and medium-sized enterprises, in particular in sectors of the knowledge-intensive services. The shortage of qualified personnel is beginning to represent a threat to the innovative potential of Germany. We urgently need to develop our universities and research institutions and to adopt intelligent, targeted immigration policies. The Expert Commission also considers the questions relating to the implementation of the Second Recovery Package. This requires particularly rapid and effective action. – – Die im Auftrag der deutschen Bundesregierung tätige Expertenkommission Forschung und Innovation legt hiermit ihr zweites Gutachten vor. Nach der Abfolge der Gutachten sollte es eigentlich ein ,kurzes' Gutachten sein, in dem zentrale Indikatoren von Forschung und Entwicklung fortgeschrieben und kommentiert werden. Die Expertenkommission hat sich entschlossen, weit mehr als das zu leisten, und empfiehlt eine Reihe von Maßnahmen zur weiteren Stärkung der Innovationskraft Deutschlands. Gerade in der heutigen, wirtschaftlich schwierigen Zeit muss die Forschungs- und Innovationspolitik eine zentrale Rolle spielen. Die Herausforderungen sind vielfältig und im Gutachten 2008 bereits benannt worden. Die Rahmenbedingungen für die Finanzierung von Innovationen sind in Deutschland weiterhin nicht optimal. Die Schwächen des Bildungssystems wirken sich bereits jetzt negativ aus und können mittelfristig zu einer existenziellen Bedrohung der Innovationsfähigkeit werden. Die hochgradige Spezialisierung auf wenige Branchen der Industrie ist ein Ausdruck besonderer deutscher Stärken, schafft aber auch Abhängigkeiten und Risiken. Da Forschungs- und Innovationspolitik mittel- und langfristig greift, können diese Probleme nicht innerhalb kurzer Zeit gelöst werden. Die Politik muss aber zügiger als bisher handeln. Die Möglichkeit der Einführung einer steuerlichen Förderung von Forschung und Entwicklung ist leider noch nicht wahrgenommen worden, und die von der Bundesregierung verabschiedeten Maßnahmen zur Verbesserung der Beteiligungsfinanzierung überzeugen in keiner Weise. In diesem zweiten Gutachten sprechen wir weitere Handlungsfelder an: die Intensivierung des Wissens- und Technologietransfers, die Steigerung der Attraktivität des Arbeitsmarktes Wissenschaft sowie die Förderung von Innovationsprozessen in kleinen und mittleren Unternehmen, insbesondere in Branchen der wissensintensiven Dienstleistungen. Der Fachkräftemangel wird zu einer Bedrohung der Innovationskraft Deutschlands. Dringend brauchen wir den Ausbau unserer Hochschulen und eine kluge, gezielte Einwanderungspolitik. Die Expertenkommission widmet sich auch Fragen der Umsetzung des Konjunkturpakets II. Hier bedarf es besonders schnellen und nachhaltigen Handelns.
Keywords: 330; Innovation; Forschung; Technischer Fortschritt; Deutschland